Association Between Safety Behaviour, Compliance with Personal Protective Equipment, and Occupational Health and Safety Performance among Dump Truck Drivers at PT. X, Samarinda - Andi Farhan Said; Iwan Muhamad Ramdan; Ida Ayu Indira Dwika Lestari (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Occupational Health and Safety (OHS) implementation in mining operations aims to minimize accidents and occupational diseases. Among dump truck drivers, Behavior toward safety and compliance with personal protective equipment (PPE) use are critical behavioral determinants of OHS performance. However, these factors are often influenced by routine, work pressure, and organizational culture. This study aimed to analyze the relationship between workers’ attitude and compliance with PPE use and OHS performance among dump truck drivers at PT. X Samarinda. Objective : To analyze the relationship between safety behavior and compliance with personal protective equipment (PPE) toward occupational health and safety (OHS) performance among dump truck drivers at PT. X Samarinda. Research Methods/ Implementation Methods : A quantitative study using a cross-sectional design was conducted among 39 dump truck drivers selected through total sampling. Data were collected through validated questionnaires and analyzed using the Spearman Rank correlation test to determine the relationship between safety behavior, PPE compliance, and OHS performance. Results : The majority of respondents were male and aged 30–39 years. Most demonstrated a high level of PPE compliance (82.1%) but a moderate level of safety behavior. The analysis revealed a significant positive relationship between both safety behavior (p < 0.05) and PPE compliance (p < 0.05) with OHS performance. Workers who exhibited a positive safety behavior and consistently used PPE demonstrated better safety performance outcomes. Conclusion/Lesson Learned : Safety behavior and PPE compliance are key behavioral components that significantly affect OHS performance. To enhance sustainable safety behavior, it is recommended that the company apply Behaviour-Based Safety (BBS) strategies such as regular observation of safe and unsafe acts, peer feedback, reinforcement of positive safety behaviors, and participatory safety talks to strengthen workers’ internal motivation and safety culture.